The Study of Security Priming on Avoidant Attentional Biases: Combining Microsaccadic Eye-Movement Measurement With a Dot-Probe Task - Mellor, Rebecca Louise; Psouni, Elia (Frontiers in Psychology, 2021)
Microsaccades are small fixational eye movements that have shown to index covert attentional shifts. The present experiment combined microsaccades with performance measures from a dot-probe task to study influences of attachment security priming on the attentional biases of individuals high in attachment avoidance. Security priming is an experimental manipulation aimed at boosting felt security. Using a randomized, mixed design, we measured differences in attentional vigilance towards angry and neutral faces as a function of priming (neutral vs. secure) and attachment avoidance. Individuals high in avoidance habitually tend to withdraw from, or otherwise dismiss, emotionally salient stimuli. Here, we operationalized attentional withdrawal based on both task performance in the dot-probe task, and microsaccadic movements. In addition, unlike previous studies where priming salience for the individual participant has been unclear, we used a standardized narrative method for attachment script assessment, securing an indication of how strongly each participant was primed. Dot-probe data significantly captured the link between avoidance and attentional disengagement, though from all facial stimuli (angry and neutral). Although microsaccadic movements did not capture avoidant attentional disengagement, they positively correlated to dot-probe data suggesting measurement convergence. Avoidance was associated with weaker security priming and no overall effect of priming on attention was found, indicating a need for further exploration of suitable priming methods to bypass avoidant deactivation. Our results provide a first indication that, as an implicit looking measure, microsaccadic movements can potentially reveal where early attention is directed at the exact moment of stimulus presentation.